Desarrollo de una propuesta de mejora al proceso de producción de bujes y mangueras en la empresa I.N.R. Inversiones Reinoso y Cía. Ltda (2018)
The present work of degree contains a total diagnosis of the manufacturing process of rubber bushings and hoses manufactured by the company INR Inversiones Reinoso & Cía. Ltda. Widely used in the automotive industry as an alternative to reduce repair costs compared to original spare parts. This company is forced to produce more than 10,000 pieces to be able to supply the demand that we have at this moment for what its online production is strongly verified by its quality management department, where it has been found that approximately 15% of the monthly production is being declared as nonconforming product, since rubber is present in the products made in the company in the circumstances in which there are imperfections, in which it is necessary to make a diagnosis in the production process to find the faults in the same and thus to be able to avoid this problem it continues being presented because it is representing the time of the work and the raw material quite considerable for the economy of the company. In this case, this degree project results, through the analysis, in the moment, at the time of the set, and the vulcanization of the rubber, and the use, in the laboratory, under the ASTM standards. present in the process to develop a proposal for improvement to obtain a better quality product by reducing losses in the process. Keywords: bushings, rubber, vulcanization, automotive, nonconforming product, design of experiments.